Progressive collapse resistance mechanism of RC frame structure considering reinforcement corrosion - Bao, Chao; Lv, Dahai; Wang, Huxiang; Zhang, Yuhang; Ma, Xiaotong; Lim, Kar Sing; Zhang, Juping (Hindawi Publishing Corporation, 2023)
Corrosion causes reduction in cross-sectional area of reinforcement, deterioration of mechanical properties, and degradation of bonding properties between reinforced concrete, which are the most important factors leading to the degradation of structural service performance. In order to investigate the progressive collapse mechanism of a corroded reinforced concrete frame structure, the failure modes, characteristics of the vertical displacement, and load capacity are studied using the finite element method. Based on existing experimental research, the established model is verified, and the influence of different influencing factors on the progressive collapse mechanism is analyzed. The results show that the corrosion of the reinforcement affects the yield load, peak load, and ultimate load of the reinforced concrete substructure. As the corrosion rate increases, the tensile arch action shows a particularly severe deterioration. The variation of concrete strength and the height–span ratio affects the substructure’s load-bearing capacity much more significantly than the stirrup spacing.